Manajemen Kinerja Berdasarkan Pendidikan dan Pelatihan, Masa Kerja dan Konsep Diri Guru SMA Negeri Se-Kabupaten Bima - Arifnaldi, Arifnaldi; Purnasari, Agustina Sri (Universitas Sarjanawiyata Tamansiswa, 2024)
This research aims to (1) determine the influence of education and training, years of service and teacher self-concept on the performance of public high school teachers in Bima Regency; (2) To determine the effect of education and training on the performance of public high school teachers in Bima Regency; (3) To determine the effect of work experience on the performance of public high school teachers in Bima Regency; (4) To determine the influence of teacher self-concept on the performance of State High School teachers in Bima Regency. This type of research uses quantitative research, using survey methods. The population in this study were State High School teachers throughout Bima Regency with a sample of 340 teachers from 4 schools determined using the Slovin formula. To analyze the data using simple linear regression and multiple linear regression. Data assumption tests consist of normality tests, linearity tests and multicollinearity tests. Based on the results of data analysis, it can be concluded that education and training, years of service and teacher self-concept have a positive and significant influence on the performance of State High School teachers throughout Bima Regency, both partially and simultaneously. The results of this study not only provide academic insight into the factors that influence teacher performance, but can also be used as a basis for decision making for schools and governments in improving the quality of education. Better training, richer work experience, and positive self-concept will produce more professional teachers and better-quality education.